Discrimination and avoidance due to disability in Australia: evidence from a National Cross Sectional Survey - Temple, Jeromey B. (BMC Public Health, 2018)
BACKGROUND: Across most high-income countries, populations are ageing. With this demographic change is an increase in the number of people living with disabilities. In this context, we sought to examine the prevalence of disability discrimination and disability avoidance in Australia, the demographic and health correlates of exclusion and the contexts in which disability discrimination and avoidance are experienced. Methods: Utilising newly released measures from the 2015 ABS Survey of Disability, Ageing and Carers, we calculate the prevalence of people living with a disability who have experienced discrimination and engage in avoidance behaviours, and the contexts in which they occur. Logistic regression models were fitted to examine the correlates of discrimination and avoidance behaviours, once controls and complex survey design were accounted for. RESULTS: Approximately 9% (95% CI = 8.1, 9.2) of people with a disability experienced disability discrimination in 2015 and 31% (95% CI = 30.9, 32.9) engaged in avoidance behaviours because of their disability. With controls included, the prevalence of avoidance and discrimination declined with age, was higher for divorced people (versus married), the unemployed (versus employed) and was lower for people with lower levels of education (versus a degree) and those born overseas. Having a psychosocial or physical disability significantly increased the odds of experiencing discrimination or avoidance, as did having an increasing number of long-term health conditions. We further find that disability discrimination and avoidance occurs in contexts critical to human capital, such as the workforce, education and healthcare. CONCLUSIONS: Despite protections in legislation and international accords, significant proportions of Australians with a disability experience discrimination or engage in avoidance behaviours in various settings with potentially important human capital implications. Recently, sectoral responses (eg., in education and the workplace) have been offered by Government reports, providing direction for future research and evaluation.